Contributing factors that affect employee’s motivation at workplace in Saj Holdings Sdn Bhd Muar / Nor Zarina Mohd Badarun - Mohd Badarun, Nor Zarina (Faculty of Business and Management, 2009)
Employee motivation is a major factor in the success or failure for any organization. Thus, these research aims to see the employee’s motivation at workplace in SAJ Holding Sdn. Bhd Muar since these company involve in water supply industry and employee’s motivation become as an critical aspects to be maintain in order to be competitive. Thus four independents variables were tested to see it relationship with employee’s motivation which is compensation, working condition, recognition, and training and development. The objectives of the research is to determines factors that related to employee’s motivation, to determines the level of strength between independent variables and dependent variables and also to determine what are the most factor that influencing employee’s motivation at workplace. These research paper was used the correlation study. Correlational study is when the researcher is interested in delineating the important variables associated with the problem. Furthermore data collection method that was used is questionnaire and also observation. The data was collected from 85 respondents that come from various job positions which are executive, clerks, technician, crew, operator logy, and meter reader. In this research study, the sampling technique used is probability sampling because elements in the population have a known chance of being chosen as subjects in the sample. This research also used the stratified sampling which simple random sub samples are drawn from within different strata that are more or less equal on some characteristics. From the findings that revealed through Pearson correlation analysis, it state that only three independent variable have significant relationship with employee’s motivation at SAJ Holdings Sdn Bhd Muar which is compensation, working condition, and also recognition. While the results from regression backward analysis indicated that the recognition become as the most factor that affects employee’s motivation at workplace.